STARLINK, PLANETARY CAPITALISM AND CONTEMPORARY IMAGINARIES OF THE AMAZON - Cruz Lobato, Luisa; de Castro, Brenda (AoIR Selected Papers of Internet Research, 2026)
Our work analyzes public documents, social media publications, media reports and interviews on the operation of Starlink in the Amazon to investigate the role of contemporary digital infrastructures in advancing projects of capitalist occupation and exploitation of the Brazilian Amazon. We identify hegemonic discourses surrounding the role of digital technologies in the economic and social development of the region and look at how these discourses resonate with 19th and 20th centuries projects of occupation for the region via ‘civilization’ and technological progress. We argue that this technophilic view does little to support sustainable and fair development: by remaining silent about the connections between digital infrastructures and the exploitation of local bodies and territories, it obstructs visions of the future that consider interdependent ways of life that escape the hegemonic imaginary of capitalist domination. At the same time, we discuss some of the ambivalent ways in which Starlink has been used and re-purposed by local communities.